The Role of Telecardiology in Dealing with Patients with Cardiac Rhythm Disorders in Family Medicine - Systematic Review - Vodička Staša; Naji Husam Franjo; Zelko Erika (Sciendo, 2020)
Heart rhythm disorders (HRD) are often present in patients visiting their family physician (FP). Dealing with their problems is not always simple, efficient and cost effective. The aim of this paper is to review the existing literature about the use and experience of telecardiology in patients experiencing HRD.